INFLUENCE OF DOUBLE SOLUTION TREATMENT ON HARDNESS IN 17-4 PH STEEL - R. Sowa; E. Roga; S. Arabasz; A. Dziedzic; I. Dul; A. Kowal; M. Parlinska-Wojtan (Journal of Engineering & Processing Management, 2015)
The investigated material is a corrosion-resistant, Cu precipitation hardened steel 17-4PH,which undergoes a macroscopic contraction, as a result of applying the following heat treatment:double solution treatment at 1028 ℃ for 1 h (condition A), ageing at 540 ℃ for 4 h (conditionH1025). The second solution treatment at 1028 ℃ was found to eliminate the retained austenite,being the evidence of a completely finished martensitic transformation.Indeed, the only phaseidentified in all samples was fcc lath martensite exhibiting a parallel striped structure.Unfortunately, this additional heat-treatment operation leads likewise to significant and irregulargrain growth, which consequently causes a drop in material hardness. Moreover, the secondsolution annealing, caused a shift in the XRD peaks to higher 2θ angles, resulting from a latticeparameter decrease by 0,25%. The two subsequent heat-treatment procedures bring the latticeparameter back to its initial value. This seemingly reversible process of decrease and increase of thelattice parameter was observed for samples subjected to all the heat treatment operations, stronglysuggesting the existence of a relation between the microstructural changes and the macroscopiccontraction of the steel material. In addition to the martensitic phase, in the unaged samples, a δ-ferrite phase could be identified by TEM and electron diffraction, which is favorable for ductilityand toughness of the material. In all samples, non-coherent fcc-NbC precipitates identified byelectron diffraction and EDX mapping having sizes up to 70 nm were found.
Keywords: steel 17-4PH; retained austenite reduction; Cu precipitation hardening; δ-ferrite; NbC precipitates; TEM